2023
DOI: 10.3389/fnins.2023.1141261
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of peripheral cytokines, BDNF, and surface-based morphometry indices in T2DM patients without cognitive impairment

Abstract: PurposeThis study aimed to investigate potential biological mechanisms underlying cognitive function alterations in Type 2 diabetes mellitus (T2DM) patients by integrating cortical morphology with peripheral cytokine levels and brain-derived neurotrophic factor (BDNF) levels, and to offer potential insights for the early detection of T2DM-related cognitive impairment.MethodsThis study included 16 T2DM patients with a Montreal Cognitive Assessment (MoCA) score of at least 26 points, as well as 16 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…AD, the most prevalent neurodegenerative disease, has been reported to have enhanced genotypic effects of the proteins SPI1 and CD33 encoding proteins at the AD inflammation-related SNP locus as peripheral blood CRP levels increase, and an increased risk of conversion to AD in people with mild cognitive impairment (MCI) ( Huang J. et al, 2022 ). One study ( Lyu et al, 2023 ) demonstrated that by comparing diabetic (T2DM) patients aged 29–65 years who did not meet the criteria for a clinical diagnosis of cognitive impairment with the normal population (42.125 ± 10.436 years), although the difference did not gain statistical significance, the Montreal cognitive assessment scale (MoCA) scores of the T2DM patients showed a tendency to be lower than that of healthy controls and peripheral blood laboratory results showed significantly lower levels of peripheral blood IL-4 and brain-derived neurotrophic factor (BDNF) in the T2DM population compared to the healthy population. Suggesting that peripheral blood cytokines and BDNF may have been altered in T2DM patients before the onset of cognitive deficits.…”
Section: Peripheral Inflammation and Neurocognitive Impairmentmentioning
confidence: 99%
“…AD, the most prevalent neurodegenerative disease, has been reported to have enhanced genotypic effects of the proteins SPI1 and CD33 encoding proteins at the AD inflammation-related SNP locus as peripheral blood CRP levels increase, and an increased risk of conversion to AD in people with mild cognitive impairment (MCI) ( Huang J. et al, 2022 ). One study ( Lyu et al, 2023 ) demonstrated that by comparing diabetic (T2DM) patients aged 29–65 years who did not meet the criteria for a clinical diagnosis of cognitive impairment with the normal population (42.125 ± 10.436 years), although the difference did not gain statistical significance, the Montreal cognitive assessment scale (MoCA) scores of the T2DM patients showed a tendency to be lower than that of healthy controls and peripheral blood laboratory results showed significantly lower levels of peripheral blood IL-4 and brain-derived neurotrophic factor (BDNF) in the T2DM population compared to the healthy population. Suggesting that peripheral blood cytokines and BDNF may have been altered in T2DM patients before the onset of cognitive deficits.…”
Section: Peripheral Inflammation and Neurocognitive Impairmentmentioning
confidence: 99%